Determinan Kinerja Keuangan Perusahaan: Pengaruh Proporsi Direksi Wanita, Proporsi Komisaris Wanita, Ukuran Direksi, dan Likuiditas pada Perusahaan Indeks IDX30 Periode 2020–2024 - Refael Putra Handoko; Tri Kartika Pertiwi (Jurnal Riset Pendidikan Ekonomi, 2026)
The intensifying business competition requires companies to continuously improve their financial performance for the company to continue make business. Studies has found new strategies in the execution of strong corporate governance practices, particularly regarding the composition of the board of directors and liquidity oversight. However, awareness of the potential of women’s leadership in Indonesia remains relatively limited, resulting in suboptimal findings, thereby underscoring the importance of further academic research. Therefore, this research purpose is to examine the impact of the proportion of female directors and commissioners, board size, and liquidity on company profitabily performance—proxied by ROA and ROE—using regression analysis. The data derived from list of business in the IDX30 index during the 2020–2024 period. The findings indicate that the proportion of female directors has a positive effect on ROA and ROE. Conversely, the proportion of female commissioners does not show a significant effect on ROA but has a positive effect on ROE. Board size shows a negative relationship with ROA and ROE, while liquidity does not have an impact on either of these performance metrics. These results underscore the important role of board composition in shaping corporate performance.